Media-based quantitative content analysis of death and injury incidents involving generation Y and Z adolescents - Erk, Mehmet Aykut; Fırat, Sunay (The Bulletin of Legal Medicine, 2025)
Objective: Violence is a broad and multidimensional phenomenon. Research in the field has long exhibited considerable variation in how violence is measured, defined, and categorized; the absence of a shared definition has led to significant challenges in both theoretical and practical contexts. The aim of this study is to analyze news reports on physical violence involving adolescents in Turkey, evaluate these incidents based on generational differences, and identify potential factors influencing violent behavior. Methods: The study employed a quantitative content analysis of online news reports selected according to predefined criteria. The sample was drawn from news articles corresponding to the adolescence periods of Generation Y and Generation Z. This design enabled a comparative analysis between the two cohorts. Results: The average age of adolescents who perpetrated acts of physical violence was found to be similar across generations (Gen Y: 16.14; Gen Z: 16.39). However, the average age of victims differed significantly between cohorts (Gen Y: 22.47; Gen Z: 24.59). Physical violence incidents were most frequently reported in the spring months and appeared to increase in newly urbanized areas. The context, motivation, and severity of violence showed statistically significant differences across generations. Conslusion: The increased use of social media and digital platforms among Generation Z has intensified the pursuit of social approval through content production. This trend appears to contribute to a rise in physically violent incidents carried out in exchange for online attention or approval. It is recommended that parents enhance their digital and media literacy skills .